Five decades of clinical assessment of whole-sporozoite malaria vaccines - Nunes-Cabaço, Helena; Moita, Diana; Prudêncio, Miguel (Frontiers in Immunology, 2022)
In 1967, pioneering work by Ruth Nussenzweig demonstrated for the first time that irradiated sporozoites of the rodent malaria parasite Plasmodium berghei protected mice against a challenge with infectious parasites of the same species. This remarkable finding opened up entirely new prospects of effective vaccination against malaria using attenuated sporozoites as immunization agents. The potential for whole-sporozoite-based immunization in humans was established in a clinical study in 1973, when a volunteer exposed to X-irradiated P. falciparum sporozoites was found to be protected against malaria following challenge with a homologous strain of this parasite. Nearly five decades later, much has been achieved in the field of whole-sporozoite malaria vaccination, and multiple reports on the clinical evaluation of such candidates have emerged. However, this process has known different paces before and after the turn of the century. While only a few clinical studies were published in the 1970’s, 1980’s and 1990’s, remarkable progress was made in the 2000’s and beyond. This article reviews the history of the clinical assessment of whole-sporozoite malaria vaccines over the last forty-nine years, highlighting the impressive achievements made over the last few years, and discussing some of the challenges ahead.